Detection of pathogenic Escherichia coli and microbiological quality of chilled shrimp sold in street markets - Barbosa, L. J. [UNESP]; Ribeiro, L. F. [UNESP]; Lavezzo, L. F. [UNESP]; Barbosa, M. M.C.; Rossi, G. A.M. [UNESP]; do Amaral, L. A. [UNESP] (Oxford University Press (OUP), 2016)
Foodborne illnesses caused by Escherichia coli are one of the most important gastrointestinal diseases and therefore represent a public health risk. The presence of E. coli in water or in products such as shrimp indicates faecal contamination. However, indicator micro-organisms can be used to evaluate the microbiological quality of food sold in markets. This study focused on detecting isolates of E. coli containing the genes stx1A, stx2A, eae, LTI, STa, STb, aggR and pCVD432 in chilled shrimp sold in street markets in the municipality of São Paulo, Brazil, and to assess the microbiological quality of this product. Enteropathogenic and enterotoxigenic E. coli pathotypes were detected on the surface of two chilled shrimp samples. Salmonella spp. was not isolated. In addition, contamination of surface and muscle of the shrimp samples was found to be correlated. The detection of EPEC and ETEC pathotypes in chilled shrimp sold in street markets in Brazil provides useful epidemiological information for public health authorities to improve food safety and public health. Significance and Impact of the Study: Shrimps are crustaceans commonly produced and consumed in Brazil. Specimens of Farfantepenaeus brasiliensis and Litopenaeus schmitti sold in street markets were examined by PCR to detect the presence of Escherichia coli pathotypes (enteropathogenic, enterotoxigenic, enterohemorrhagic and enteroinvasive). EPEC and ETEC strains were detected in whole shrimp. These findings provide useful information for public health authorities to improve the food safety and health of the Brazilian population.
Keywords: Escherichia coli; Salmonella; Enteropathogenic E. coli; Enterotoxigenic E. coli; Microbiological quality; Shrimp